Effect of microstructure on the dielectric properties of poly(vinyl alcohol)–poly(3, 4‐ethylenedioxythiophene) doped with poly(styrenesulfonate) composite films. Issue 34 (15th May 2017) - Mydhili, V.; Manivannan, S.
ABSTRACT: Poly(3, 4‐ethylenedioxythiophene) doped with poly(styrenesulfonate) (PEDOT–PSS) was blended with poly(vinyl alcohol) (PVA) to form 0, 10, 20, 30, 40, and 50 vol % PEDOT–PSS/PVA solutions, and their freestanding films were prepared with a simple and cost‐effective solution casting technique at 27 °C in the absence of additives. Field emission scanning electron microscopy images revealed changes in the cocontinuous network to a rodlike morphology in the composite films from 10 to 50 vol % PEDOT–PSS/PVA. The alternating‐current conductivity was found to obey Jonscher's power law. The obtained values of the dielectric constant at 27 °C were relatively high, and a maximum value of 6.7 × 10 4 at 100 Hz for 40 vol % PEDOT–PSS'/PVA was observed. The dielectric loss attained a maximum value of about 10 6 at 100 Hz for 40 vol % PEDOT–PSS/PVA. However, a decrease in the dielectric parameters was observed at 50 vol % PEDOT–PSS/PVA because of locally induced strain in the microstructure. The variations in polarization with respect to the applied electric field (P–E) were determined for 50, 100, and 500 Hz at 500 V for the freestanding composite films of lower concentrations up to 20 vol % PEDOT–PSS/PVA. In summary, the dielectric and P–E measurements confirmed that the electrical characteristics changed in accordance to the contribution from both resistive and capacitive sites in the PEDOT–PSS/PVA composites. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45079. Abstract :